Penerapan model pembelajaran RME untuk meningkatkan keterampilan berpikir kritis matematika siswa kelas V sekolah dasar - Dewi, Ninik Sarwini Raga; Kamsiyati, Siti; Surya, Anesa (Universitas Sebelas Maret, 2020)
Critical thinking is one of the skills of High Order Thinking Skills (HOTS) which is the goal of the 2013 curriculum. But, 102 Totosari State Elementary School students still have a low critical thinking level. This research aimed to improve student’s critical thinking by implementing RME (Realistic Mathematics Education) learning model for 5th Grade 102 Totosari Elementary School Students Surakarta Academic Year 2019/2020. This research used Classroom Action Research as the method and it formed of two cycles. Each cycle consisted of four steps: planning, implementing, observing, and conducting reflection. The participant of the research is 24 students of 5th-grade 102 Totosari State Elementary School Surakarta Academic Year 2019/2020. The teacher, critical thinking data score, and other documents became the data source. Source and technique triangulation used to check data validity. Data analysis used the interactive analysis model consisted of three components including data reduction, data presentation, and conclusion.This result showed that the critical thinking level of 5th-grade students increased through the implementation of the RME learning model. The improvement evidenced from the students’ actions until the second meeting of second cycles. The result showed an 83% improvement of 8% pre-action. This research can be used as a source in other studies in improving critical thinking skill.